Front Cover - Ohlsson, Bodil (Clin Case Rep, 2020)
The cover image is based on the Case Report Autonomic and peripheral neuropathy with reduced intraepidermal nerve fiber density can be observed in patients with gastrointestinal dysmotility by Bodil Ohlsson, Béla Veress, LARS B DAHLIN et al., https://doi.org/10.1002/ccr3.2575. [Image: see text]